ENHANCING DIABETES CARE: EVALUATING THE EFFICACY OF TELEMEDICINE FOR INITIATING INSULIN THERAPY IN TYPE 2 DIABETES PATIENTS AT GRAND HANTHA DIABETES CENTER, MYANMAR - Aye, Than Than; Pyone, Mie Mie; Zaw, Thet Htun; Aung, Ei Zarni; Han, Aye Moh Moh (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Amidst the COVID-19 outbreak in Myanmar, telemedicine has emerged as a crucial tool, enabling healthcare providers to conduct remote assessments, offer patient education, and provide guidance on initiating insulin therapy. Insulin therapy plays a vital role in managing uncontrolled diabetes with secondary oral antidiabetic (OAD) treatment failure. Its effectiveness in controlling blood glucose levels is wellknown. However, there remains a concern about the risk of hypoglycemia and timely titration to reduce therapeutic inertia, particularly for individuals residing in remote districts where access to healthcare professionals (HCPs) is limited. In such challenging circumstances, junior doctors from diabetes centers supported patients throughout the initial three-month period of insulin initiation, providing valuable guidance and care. This study aims to ascertain the effectiveness and safety of initiating insulin therapy guided by experienced Medical Officers of GHDC (Grand Hantha Diabetes Center) using the Viber app on mobilephones, which is widely available and accessible in remote areas of Myanmar. METHODOLOGY A prospective three-month follow-up study was conducted on patients initiated on insulin therapy due to oral hypoglycemic agent (OHA) failure. These patients were enrolled in the GHDC and voluntarily participated in the study from March 2022 to June 2022. In total, 85 patients underwent assessments for pre-HbA1c and post-HbA1c levels, average fasting blood glucose (FBG) and average random blood sugar (RBS) levels (including postprandial blood sugar [PPBS] and pre-meal levels) during the duration of the study. Additionally, severe hypoglycemia, defined as blood glucose levels below 54 mg/dl or instances where assistance was required for recovery, was also noted. RESULTS Overall, consultations via the Viber app led to improvements in FBG and RBS during the second and third months compared to the first month, along with a significant reduction in HbA1c levels. Among the patients, 27 patients (32%) achieved a reduction of HbA1c less than 10% from the baseline, 28 patients (33%) achieved a reduction between 10% and 30%, and 17 patients (20%) achieved a reduction of over 30% from the baseline. Thirteen patients (15%) showed either an increase or no change in their results compared to the baseline. There was a satisfactory reduction in the following parameters: FBG decreased from a mean baseline of 167 to 129, Postprandial blood sugar decreased from 223 to 162, and premeal blood sugar decreased from 212 to 152. Among these patients, eight patients (9%) experienced hypoglycemic symptoms and required the intake of sugary drinks to alleviate the condition. None required admission. CONCLUSION Telemedicine is effective and safe for initiating insulin therapy in Type 2 Diabetes Patients during the COVID-19 outbreak.